2021
DOI: 10.1186/s12913-021-06582-2
|View full text |Cite
|
Sign up to set email alerts
|

Personal barriers to addressing intimate partner abuse: a qualitative meta-synthesis of healthcare practitioners’ experiences

Abstract: Background Healthcare practitioners (HCPs) play a crucial role in recognising, responding to, and supporting female patients experiencing intimate partner abuse (IPA). However, research consistently identifies barriers they perceive prevent them from doing this work effectively. These barriers can be system-based (e.g. lack of time or training) or personal/individual. This review of qualitative evidence aims to synthesise the personal barriers that impact HCPs’ responses to IPA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…Studies exploring the perceptions of HCPs consistently indicate that this fear is a very real barrier to enquiry and response. 15 Given that a range of clinical conditions may be caused or complicated by IPA, including chronic pain, suicidal ideation, gynaecological issues, depression and addiction, asking about patient exposure is highly relevant to the medical encounter and the provision of appropriate healthcare support. 1 6 10 Children also experience detrimental effects from IPA exposure, and studies indicate that children are a significant factor in women’s decisions to seek professional support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies exploring the perceptions of HCPs consistently indicate that this fear is a very real barrier to enquiry and response. 15 Given that a range of clinical conditions may be caused or complicated by IPA, including chronic pain, suicidal ideation, gynaecological issues, depression and addiction, asking about patient exposure is highly relevant to the medical encounter and the provision of appropriate healthcare support. 1 6 10 Children also experience detrimental effects from IPA exposure, and studies indicate that children are a significant factor in women’s decisions to seek professional support.…”
Section: Discussionmentioning
confidence: 99%
“… 15 16 These include a reluctance to interfere in a patient’s ‘private’ issues, frustration and feelings of helplessness when patients do not take their advice, and resistance to taking responsibility for dealing with IPA. 15 …”
Section: Introductionmentioning
confidence: 99%
“…[ 50 51 ] Even in European countries family physicians and health care workers reported the hurdles in addressing such abusive events. [ 52 ] The need to develop policies and awareness campaign to know own rights and being assertive to report abusive incidents are inevitable.…”
Section: Methodsmentioning
confidence: 99%
“…There are many barriers to inquiry by health practitioners and disclosure by victims/survivors 19‐21 . A systematic review of 35 quantitative studies suggested low rates of routine domestic violence screening by practitioners (with the majority reporting between 10% and 20%) 22 From meta‐syntheses of qualitative studies, we know that health practitioners experience personal and structural barriers to domestic violence inquiry and response.…”
Section: Barriers To Inquiry and Disclosurementioning
confidence: 99%
“…A systematic review of 35 quantitative studies suggested low rates of routine domestic violence screening by practitioners (with the majority reporting between 10% and 20%) 22 From meta‐syntheses of qualitative studies, we know that health practitioners experience personal and structural barriers to domestic violence inquiry and response. Personal barriers include practitioners feeling they “can’t interfere” as domestic and sexual violence are private issues, “don’t have control” over outcomes for victims/survivors, and “won’t take responsibility” as it is someone else’s role 20 . At the structural level, practitioners perceive that “the environment works against us” with lack of time and spaces, they are “trying to tackle the problem on their own” without a team behind them, and “societal beliefs enable us to blame the victim” 19 .…”
Section: Barriers To Inquiry and Disclosurementioning
confidence: 99%